America's untold story [videorecording (DVD)] - Gordon, Robbie (Television producer); Gordon, Robbie (Television producer); Smits, Jimmy; Deagan, Kathleen A.; Colburn, David R.; Roberts, Churchill Lee, 1940-; Parker, Susan R.; Gannon, Michael, 1927-2017; Francis, J. Michael (John Michael); Hunt, Roy (PBS Distribution, 2018)
First permanent European settlement in the United States was founded two generations before the Pilgrims arrived in 1565. America's Untold Story uncovers the story of America's past that never made it into textbooks.